Mangrove species diversity and carbon stock in silvofishery ponds in Deli Serdang District, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Harefa MS, Nasution Z, Mulya MB, Maksum A. 2021. Mangrove species diversity and carbon stock in silvofishery ponds in Deli Serdang District, North Sumatra, Indonesia. Biodiversitas 23: 655-662. Mangrove-based silvofishery ponds are promoted as a win-win solution for biodiversity conservation, climate change mitigation as well as income generation for coastal communities. This study aimed to analyze the species diversity and carbon stock of mangrove vegetation in silvofishery ponds in Tanjung Rejo Village, Percut Seituan Sub-district, Deli Serdang District, North Sumatra, Indonesia. Data of the mangrove species were obtained using vegetation analysis, and the potential carbon stock was estimated based on allometric equations of both above- and below-ground tree biomass. For this purpose, plot samples from 22 silvofishery ponds were taken by establishing 5 aligned circular plots, each with a radius of 5.64 m, perpendicular to the coastline and with a distance of 15 meters between their perimeters. The results show that the mangrove species with the highest Importance Value Index (IVI) was Rhizophora apiculata (122.05%), followed by Excoecaria agallocha (42.29%) and Avicennia marina (36.84%), and the lowest IVI was Sonneratia caseolaris (1.48%). Higher IVI values indicate a larger carbon deposit from mangrove vegetation in silvofishery ponds. Our results indicate that mangrove area coverage of 44-80% per hectare in silvofishery ponds can deposit 40-50 tonnes of carbon per hectare and have greater potential carbon stock compared to coverage below 40%. The mangrove management activities with the sylvofishery scheme have a good impact on the community's economy and also maintain the existence of mangroves as carbon storage.